The energy and fat digestibility of finisher phase broiler with different feeding frequency. Issue 1 (1st December 2022) - Faradila, S.; Nuraeni; Aulyani, T. L; Azhar, M.; Sara, U.
Abstract: This study aims to determine the digestibility of energy and fat in finisher phase broiler with different feeding frequency. The study method was arranged based on a completely randomized design (CRD) with 4 treatments and 4 replications where each replication consisted of 5 broilers. The treatments applied were the frequency of feeding one time (at 17.00 PM), two times (at 07.00 AM dan 19:00 PM), three times (at 07.00 AM, 15.00 PM, 23.00 PM), and four times (at 05.00 AM, 11.00 AM, 17.00 PM, 23.00 PM). The parameters observed were energy and fat digestibility. The results showed that energy and fat digestibility had no significant effect (P>0.05) on different feeding frequencies. The conclusion of this study is feeding once (P0) is more efficient to implement.